Unilateral Tubal Obstruction Associated with Contralateral Ectopic Pregnancy - Karalok, Hakan; Gürsoy, Özlem; Karalok, Ebru; Akcığ, Zeynep; Savan, Kadir (Gynecology Obstetrics & Reproductive Medicine, 2006)
Ectopic pregnancy is one of the pregnancy related complications, seem to be increased in recent years due to gradual increase in ART(Assisted Reproductive Techniques) cycles. An interesting case of unilateral tubal obstruction with contralateral ectopic pregnancy occurence is presented to our clinic. It is postulated that ectopic pregnancy occured in the contralateral part as a result of oocyte migration transperitoneally. The case is presented as 35 year-old women with a history of IVF(in vitro fertilization) treatment as a result of tubal factor infertility. In the diagnosis of ectopic pregnancy cases, the most important point is the high index of ectopic pregnancy suspicion. Ectopic pregnancies should be evaluated with associated risk factors and treated accordingly with defined protocols.